The role of laser ablation technique parameters in synthesis of nanoparticles from different target types - Naser H.; Alghoul M.A.; Hossain M.K.; Asim N.; Abdullah M.F.; Ali M.S.; Alzubi F.G.; Amin N. (Springer, 2023)
Ablation; Laser pulses; Nanoparticles; Synthesis (chemical); Laser ablation technique; Laser focusing; Medium of ablation ambient; Nanoparticle synthesis; Pulse parameter; Laser ablation; acetone; alcohol; deionized water; nanoparticle; colloid; energy; gas; laser ablation technique; liquid; particle size; plasma gas; pressure; priority journal; Review; synthesis